Evaluation of placental thickness as a sonological indicator for estimation of gestational age of foetus in normal singleton pregnancy - Kaushal, Lovely; Patil, Abhijit; Kocherla, Keerthi (International Journal of Research in Medical Sciences, 2017)
Background: Gestational age is frequently over or under estimated, as the conventional gestational estimation is based on the last menstrual period and on ultrasonography. Many people are unaware of their last menstrual period and irregular menstruation and ultrasonography is bound to have a bias, thereby posing difficulties in the estimation gestational age. Placental thickness measured at the level of umbilical cord insertion appears to be a new promising parameter for estimation of gestational age of fetus as placenta is a maternal foetal organ and its size is a reflection of the health and size of the foetus. It provides the physiological link between a pregnant woman and the fetus.Measurement of placental thickness is relatively simple and very useful. In our present study we have tried to measure Placental thickness at the level of umbilical cord and determine its relationship with gestational age of foetus in normal singleton pregnancy. Methods: The current crossectional study was conducted at the department of radiodiagnosis, Gandhi medical college and Hamidia hospital, Bhopal from April 2012 to December 2014. This is a hospital based study with a sample size of 199 normal antenatal women. All the subjects were enrolled with detailed oral and written consents. All examinations were performed using GE logic 3 expert scanner with 3.5 MHz convex array transducer. Placental thickness in millimeters was measured at the level of insertion of the umbilical cord. Data was compiled in MS excel sheet and analyzed using online statistical calculator, chi square test and pearson correlation coefficient were applied with value of P <0.05 was considered statistically significant. Results: In the total study group of 199 normal antenatal women, the age ranged between 18yrs to 34 years and the mean age was between 20 and 25 years of age. Anterior placenta was noted to be the most common location amongst the study sample. It is observed that placental thickness correlates with gestational age and gradually increases as gestational age increases. To prove that there was a correlation the between placental thickness and the gestational age, the Pearson correlation coefficient was found to be r = 0.98 and the p value was <0.001, thereby establishing a positive correlation between the two variables, indicating placental thickness measured in millimeters increases with gestational age measured in weeks and were statistically significant. Conclusion: A linear increase in mean placental thickness with gestational age was observed using correlation analysis in our present study conducted to determine the relationship between placental thickness and gestational age. Placental thickness measured in millimeters increases with gestational age from 11 weeks to 37 weeks. Placental thickness can be used as a predictor of the gestational age, in women in whom the last menstrual period is unreliable or is not known. In instances when femoral length was difficult to measure due to excessive foetal movements, Placental thickness was found to be a reliable alternative biometric measurement in calculating gestational age.